Towards a cyber ecology - Carlo Ratti; Daniele Belleri (Agathón)
This essay traces how designers are facilitating an extraordinary, double convergence between the natural and artificial worlds. After centuries of conflict, the reality of the Anthropocene and the urgency of climate change demand that we work at the intersection of our environment and our creations. Additionally, the birth of digital technologies and the Internet of Things could give us the tools to manage this interface. The first side of the coin – making the natural world into an artificially-enhanced ‘cyborg’ – has already gained momentum and cultural purchase. The other path – animating the artificial world to make it work in harmony with nature and living things – is a place where we have only just begun to take our first steps. In the design practice CRA – Carlo Ratti Associati’s firsthand work with exhibitions and experiments across the globe, often developed in collaboration with Italo Rota, we have explored two main strategies: animating the artificial with distributed computing or literally incorporating natural elements in design. Our theories are coming from our daily practice, which in turn demands new political, ecological, and evolutionary frameworks to understand the task before us.